Chapter 9 - CRISPR-Cas9 for therapy: the challenges and ways to overcome them - Sundaram Acharya; Souvik Maiti; Debojyoti Chakraborty (Genome Engineering via CRISPR-Cas9 System, 2020)
Clustered regularly interspaced short palindromic repeat/CRISPR-associated (CRISPR Cas) is a component of the prokaryotic adaptive immune system which has been repurposed for genome editing in recent years. The precision, simplicity and flexibility of this system have opened up a broad range of biological applications covering basic research to biotechnology and medicine. Additionally, the multiplexing capabilities of CRISPR offers a promising approach for modeling or correcting common polygenic disorders along with its monogenic and infectious counterparts. Although CRISPR is not completely precise and questions remain regarding its specificity and modes of delivery, the robustness and wide applicability of this genome editing tool has opened up numerous ways to address these issues. In this chapter, we will discuss about initial progress toward CRISPR therapeutics, existing delivery modalities, the challenges before CRISPR editing before it becomes a therapeutic possibility and the ongoing efforts toward developing a perfect CRISPR system for bench to bedside application.
Keywords: CRISPR therapeutics; CRISPR-Cas9; iPSC